Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Anthropology; Political Science
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

Capitalism in Transformation: Movements and Countermovements in the 21st Century - Atzmüller, Roland; Aulenbacher, Brigitte; Brand, Ulrich; Décieux, Fabienne; Fischer, Karin; Sauer, Birgit (Edward Elgar Publishing, 2019)
Presenting a profound and far-reaching analysis of economic, ecological, social, cultural and political developments of contemporary capitalism, this book draws on the work of Karl Polanyi, and re-reads it for our times. The renowned authors offer key insights to current changes in the relations between the economy, politics and society, and their ecological and social effects.
Sociology
Keywords: biography; capitalism; countermovement; fictitious commodities

Polanyi in times of populism: Vision and contradiction in the history of economic ideas - Holmes, Christopher (Routledge, 2018)
The rise of populism across Europe and the US – first in the wake of the 2008 global financial crisis and then in the shape of Donald Trump’s presidential campaign and the Brexit vote in 2016 – are indicative of a seismic shift in the terrain of economic ideas in public discourse. Settled liberal norms concerning ever-increasing international market expansion, and the political integration required to sustain it, have been decisively upset by political forces that, whilst once on the fringes, now dominate economic debate. How might we make sense of this ideological breakdown and what might we hope for next? This book turns to the work of Karl Polanyi for answers, developing the expansive, historicised approach to political economy that Polanyi pioneered. Holmes provides a wide-ranging history of economic ideas read in terms of a series of hopeful theoretical visions of order, in which political, social and ecological contradictions could be transcended in one way or another. Through this, the book demonstrates that the failing utopian visions of pre-2008 economic orthodoxy, which have formed the backdrop to the rise of populism today, are only the latest in a series that stretches across economic thought in Western modernity as a whole. This book will interest students and scholars of IPE, political science, sociology, anthropology, law and history.
Political Science
Keywords: political science / general; populism

Costly Fix: Power, Politics, and Nature in the Tar Sands - Urquhart, Ian Thomas (University of Toronto Press, 2018)
Costly Fix examines the post-1995 Alberta tar sands boom, detailing how the state inflated the profitability of the tar sands and turned a blind eye to environmental issues. It considers the position of First Nations, the character and strength of environmental critiques, and the difficulties that environmental groups and First Nations have had in establishing a countermovement to market fundamentalism. The final chapter discusses how Alberta's new NDP government, in its first couple of years, has addressed the legacies they have inherited from the previous Progressive Conservative government on climate change, royalties, and the blight of tailings ponds in the boreal forest. Throughout the book, Urquhart demonstrates that too many actors have done too little to prevent Alberta's boreal forest from becoming a landscape sacrificed for unsustainable economic growth.
Political Science
Keywords: Alberta; Canada; First Nations; double movement; environmentalism; tar sands

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Philosophy; Political Science
Keywords: boundary struggle; capitalism; political philosophy; triple movement

What American Government Does - Luger, Stan; Waddell, Brian (JHU Press, 2017)
It has become all too easy to disparage the role of the US government today. Many Americans are influenced by a simplistic anti-government ideology that is itself driven by a desire to roll back the more democratically responsive aspects of public policy. But government has improved the lives of Americans in numerous ways, from providing income, food, education, housing, and healthcare support, to ensuring cleaner air, water, and food, to providing a vast infrastructure upon which economic growth depends. In What American Government Does, Stan Luger and Brian Waddell offer a practical understanding of the scope and function of American governance. They present a historical overview of the development of US governance that is rooted in the theoretical work of Charles Tilly, Karl Polanyi, and Michael Mann. Touching on everything from taxes, welfare, and national and domestic security to the government’s regulatory, developmental, and global responsibilities, each chapter covers a main function of American government and explains how it emerged and then evolved over time. Luger and Waddell are careful to both identify the controversies related to what government does and those areas of government that should elicit concern and vigilance. Analyzing the functions of the US government in terms of both a tug-of-war and a collaboration between state and societal forces, they provide a reading of American political development that dispels the myth of a weak, minimal, non-interventionist state. What American Government Does represents a major contribution to the scholarly debate on the nature of the American state and the exercise of power in America. – Sidney Plotkin, Vassar College, coauthor of Private Interests, Public Spending: Balanced-Budget Conservatism and the Fiscal Crisis
Political Science
Keywords: American government; history - Americas (North; Central; South; West Indies); political science - history and theory

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Philosophy; Political Science
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism–R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
History; Political Science
Keywords: HENRY; Richard; PALMER; Edward; TAWNEY; R.H.; THOMPSON; E.P.; capitalism; moral and ethical aspects; moral economy; socialism

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Sociology; Political Science
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Political Science
Keywords: history - modern; political history; political philosophy; political theory

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
History
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Sociology; Political Science
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

From Keynes to Piketty: The Century that Shook Up Economics - Haan, Peter de (Springer, 2016)
From Keynes to Piketty provides the reader with an accessible and entertaining insight into the development of economic thought over the past century. Starting with John Maynard Keynes's bestseller, The Economic Consequences of Peace (1919), and ending with Thomas Piketty's blockbuster, Capital in the Twenty First Century (2014), the author explains which dramatic political and economic events changed the way economists interpreted these events, and how they revolutionized the economic science.The book contains biographies of Keynes, Schumpeter, Galbraith, Hayek, Friedman, Hirschman, North, and Piketty, alongside others, and highlights their extraordinary lives and works, anecdotes about them, and their often sharp differences of opinion. Extensive summaries of their main works provide the interested scholar and student with an accurate presentation of their contents. A must-read for all those who wonder what happened to economics during the past century, and why.
Economics
Keywords: KEYNES; John Maynard; 1883-1946; PIKETTY; Thomas; business & economics; economic history

Bourgeois Equality: How Ideas, Not Capital or Institutions, Enriched the World - McCloskey, Deirdre N. (University of Chicago Press, 2016)
There’s little doubt that most humans today are better off than their forebears. Stunningly so, the economist and historian Deirdre McCloskey argues in the concluding volume of her trilogy celebrating the oft-derided virtues of the bourgeoisie. The poorest of humanity, McCloskey shows, will soon be joining the comparative riches of Japan and Sweden and Botswana. Why? Most economists—from Adam Smith and Karl Marx to Thomas Piketty—say the Great Enrichment since 1800 came from accumulated capital. McCloskey disagrees, fiercely. “Our riches,” she argues, “were made not by piling brick on brick, bank balance on bank balance, but by piling idea on idea.” Capital was necessary, but so was the presence of oxygen. It was ideas, not matter, that drove “trade-tested betterment.” Nor were institutions the drivers. The World Bank orthodoxy of “add institutions and stir” doesn’t work, and didn’t. McCloskey builds a powerful case for the initiating role of ideas—ideas for electric motors and free elections, of course, but more deeply the bizarre and liberal ideas of equal liberty and dignity for ordinary folk. Liberalism arose from theological and political revolutions in northwest Europe, yielding a unique respect for betterment and its practitioners, and upending ancient hierarchies. Commoners were encouraged to have a go, and the bourgeoisie took up the Bourgeois Deal, and we were all enriched. Few economists or historians write like McCloskey—her ability to invest the facts of economic history with the urgency of a novel, or of a leading case at law, is unmatched. She summarizes modern economics and modern economic history with verve and lucidity, yet sees through to the really big scientific conclusion. Not matter, but ideas. Big books don’t come any more ambitious, or captivating, than Bourgeois Equality. KM - Part IV heavily engages with Polanyi's ideas, including embeddedness
Economics; Political Science
Keywords: Europe; business & economics; economic history; embeddedness; history; political science; political theory; social science

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
History; Political Science
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
History; Economics; Sociology
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Ireland, Small Open Economies and European Integration: Lost in Transition - Begg, David (International Political Economy Series., 2016)
Presents a development model for the recovery of the Irish polity post-2008 financial crisis and traces and compares the evolution of the development models of Finland, Denmark, the Netherlands, and Ireland from 1987 to 2012, considering how those four countries managed the process of Europeanization. Explores the core Polanyian tension between markets and social protection, with particular reference to the capacity of selected small, open economies to manage that tension as compared with Ireland. Discusses the world of Peter J. Katzenstein–the major historical events that contributed to the formation of the polities of Denmark, Finland, the Netherlands, and Ireland, as well as how the development models evolved as European integration intensified; 1994-2001–the age of employment miracles; 2001-08–European integration intensifies; going beyond 2008–coping with the crisis; and unpacking Ireland's polity from a new institutionalist perspective. Begg is Director of the Think Tank for Action on Social Change and former General Secretary of the Irish Congress of Trade Unions. Bibliography; index.
Economics
Keywords: current heterodox approaches: historical; economic integration; evolutionary; heterodox economics; institutional; international institutional arrangements; international political economy; open economy macroeconomics; political processes: rent-seeking; lobbying; elections; legislatures; social protection; voting behavior

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Political Science
Keywords: political theory; social theory

Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Sociology
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Law; Sociology
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM – on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Economics; Business Studies
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Political Science
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Economics; Sociology
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning

Greening of Capitalism: How Asia Is Driving the Next Great Transformation - Mathews, John (Stanford University Press, 2014)
As China, India, and other industrializing giants grow, they are confronted with an inconvenient truth: They cannot rely on the conventions of capitalism as we know them today. Western industrialism has achieved miracles, promoting unprecedented levels of prosperity and raising hundreds of millions out of poverty. Yet, if allowed to proceed unencumbered, this paradigm will do irreversible harm to the planet. By necessity, a new approach to environmentally conscious development is already emerging in the East, with China leading the way. Positioning its argument against zero-growth advocates and free-market environmentalists, Greening of Capitalism charts this transformation and sketches out a framework for more sustainable capitalism. State-mandated changes in energy use (as opposed to carbon taxes), a circular flow of resources (as opposed to emissions standards), and the introduction of new financial instruments that support green growth are cornerstones of China's framework. John A. Mathews argues that these tenets will be emulated around the worldfirst in India and Brazil. In light of this emerging shift, Mathews considers core debates over national security, international relations, and economic policy, ultimately addressing the question of whether these measures will be far-reaching or timely enough to prevent further damage.
Economics; Political Science
Keywords: business & economics; economic policy; energy; government & business; industries; public policy; sustainable capitalism

Le religioni della politica: Fra democrazie e totalitarismi - Gentile, Emilio (Gius.Laterza & Figli Spa, 2014)
La sacralizzazione della politica accade ogni volta che un'entità politica – la nazione, la democrazia, lo Stato, la razza, la classe, il partito, il movimento – è trasformata in una entità sacra, in un oggetto di devozione e di culto, ed è collocata al centro di un sistema di credenze, di simboli e di riti. Nascono allora le religioni della politica, che non si identificano con un unico tipo di ideologia e di regime: esse possono sacralizzare la democrazia o l'autocrazia, l'eguaglianza o la disuguaglianza, la nazione o l'umanità.
Philosophy
Keywords: essence of fascism; fascism; history / modern / 21st Century; political philosophy

Karl Polanyi: New Perspectives on the Place of the Economy in Society - Harvey, Mark; Ramlogan, Ronnie; Randles, Sally (Oxford University Press, 2014)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations and European labour markets.
Sociology; Economics
Keywords: business & economics; economic theory

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Sociology; Political Science
Keywords: business & economics; capitalism; economic theory

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Philosophy; Political Science
Keywords: exchange; international relations; religious philosophy; social philosophy

The Power of Market Fundamentalism - Block, Fred; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have revived from disrepute in the wake of the Great Depression and World War II, to become the dominant economic ideology of our time.Polanyi contends that the free market championed by market liberals never actually existed. While markets are essential to enable individual choice, they cannot be self-regulating because they require ongoing state action. Furthermore, they cannot by themselves provide such necessities of social existence as education, health care, social and personal security, and the right to earn a livelihood. When these public goods are subjected to market principles, social life is threatened and major crises ensue.Despite these theoretical flaws, market principles are powerfully seductive because they promise to diminish the role of politics in civic and social life. Because politics entails coercion and unsatisfying compromises among groups with deep conflicts, the wish to narrow its scope is understandable. But like Marx's theory that communism will lead to a "withering away of the State," the ideology that free markets can replace government is just as utopian and dangerous.
Sociology; Political Science
Keywords: United States history; business & economics; economic history; economic policy; economic theory; free enterprise; political economy; political science; public policy; sociology

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Sociology; Political Science
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

The Global Development Crisis - Selwyn, Benjamin (John Wiley & Sons, 2014)
The central paradox of the contemporary world is the simultaneous presence of wealth on an unprecedented scale, and mass poverty. Liberal theory explains the relationship between capitalism and poverty as one based around the dichotomy of inclusion (into capitalism) vs exclusion (from capitalism). Within this discourse, the global capitalist system is portrayed as a sphere of economic dynamism and as a source of developmental opportunities for less developed countries and their populations. Development policy should, therefore, seek to integrate the poor into the global capitalist system. The Global Development Crisis challenges this way of thinking. Through an interrogation of some of the most important political economists of the last two centuries Friedrich List, Karl Marx, Leon Trotsky, Joseph Schumpeter, Alexander Gerschenkron, Karl Polanyi and Amarta Sen, Selwyn argues that class relations are the central cause of poverty and inequality, within and between countries. In contrast to much development thinking, which portrays ‘the poor’ as reliant upon benign assistance, this book advocates the concept of labour-centred development. Here ‘the poor’ are the global labouring classes, and their own collective actions and struggles constitute the basis of an alternative form of non-elitist, bottom-up human development.
Development Studies; Political Science
Keywords: business & economics / development; economic development; embedded markets; political science / public policy / general; socialism

The Legacy of Karl Polanyi: Market, State and Society at the End of the Twentieth Century - Mendell, Marguerite; Salée, Daniel (Palgrave Macmillan UK, 2014)
The Great Transformation by Karl Polanyi, written in 1944, is a twentieth-century classic. It presents a passionate critique of the inhumanity of liberal capitalism, an inhumanity which, Polanyi thought, could never be repeated. The social and political institutions developed in the post-War period not only protected society from the cruelty of the self-regulating market, but were essential to enable the market itself to function. The history of the market, Polanyi tells us, is a history of regulation.
Economics
Keywords: Great Transformation; The (Book); business & economics; economic theory; regulation

L'économie solidaire en Bolivie. Entre marché et démocratie - Hillenkamp, Isabelle (KARTHALA Editions, 2013)
Depuis les années 1980, de plus en plus de pays ont opté pour une économie de marché et un régime politique de type démocratique et ce, indépendamment de leur « niveau de développement ». Pourtant, marché et démocratie ne sont pas directement compatibles. Si tous deux reposent sur les principes de liberté et d’égalité, le premier mise sur le pouvoir émancipateur du marché libre, alors que la seconde suppose une certaine égalité des conditions de vie. Une lecture croisée de cas européens et latino-américains illustre cette problématique commune, en même temps que la diversité des systèmes de médiations solidaires entre marché et démocratie. Les solidarités, qu’elles soient enracinées dans des structures familiales ou communautaires, instituées dans des systèmes de protection sociale ou organisées dans des groupes de producteurs ou de consommateurs de l’économie solidaire, créent en effet des interdépendances qui amortissent les tensions entre marché et démocratie. En développant cette analyse socioéconomique, Isabelle Hillenkamp propose une approche novatrice des questions de développement. Par des données récoltées auprès d’organisations d’économie solidaire et de nombreux autres acteurs en Bolivie, elle apporte des réponses ancrées dans la complexité d’un terrain de recherche. Isabelle Hillenkamp est titulaire d’un doctorat en études du développement de l’Institut de hautes études internationales et du développement, à Genève. A partir d’enquêtes en Amérique latine, ses travaux portent sur l’économie populaire et solidaire, qu’elle aborde dans une perspective socioéconomique, attentive aux liens entre pratiques économiques et rapports sociaux. Elle est chargée de recherche à l’Institut de recherche pour le développement, en France. Table des matières Introduction, L’économie solidaire en Bolivie, Entre marché et démocratie, Du pluralisme économique à la démocratisation I. Solidarité, marché et démocratie : une problématique européenne et latino-américaine II. Les organisations boliviennes d’économie solidaire : réciprocité et redistribution III. Les organisations boliviennes d’économie solidaire face aux marchés IV. Réciprocité, marché et démocratie : des tensions fondamentales V. La démocratisation de l’économie Ils en ont parlé Présentation du livre dans L'AGEFI, quotidien de l'Agence économique et financière à Genève Critique du livre sur le site Alterinfos, América Latina ENG translation: Since the 1980s, more and more countries have opted for a market economy and a democratic-type political regime, irrespective of their "level of development". Yet market and democracy are not directly compatible. If both are based on the principles of liberty and equality, the first is the emancipatory power of the free market, while the latter assumes a certain equality of living conditions. A cross-reading of European and Latin American cases illustrates this common problem, together with the diversity of solidarity-based mediation systems between market and democracy. Solidarity, whether rooted in family or community structures, instituted in social protection systems or organized in groups of producers or consumers of the solidarity economy, creates interdependencies that dampen tensions between the market and democracy. In developing this socioeconomic analysis, Isabelle Hillenkamp proposes an innovative approach to development issues. Through data collected from organizations of solidarity economy and many other actors in Bolivia, it brings answers anchored in the complexity of a field of research. Isabelle Hillenkamp holds a Ph.D. in Development Studies from the Graduate Institute of International and Development Studies in Geneva. Based on surveys in Latin America, her work focuses on the popular and solidarity economy, which she addresses in a socio-economic perspective, attentive to the links between economic practices and social relations. She is a researcher at the Research Institute for Development in France. Table of Contents Introduction, Solidarity Economy in Bolivia, Between Market and Democracy, From Economic Pluralism to Democratization I. Solidarity, Market and Democracy: A European and Latin American Issue II. Bolivian organizations of solidarity economy: reciprocity and redistribution III. Bolivian organizations of solidarity-based economy versus markets IV. Reciprocity, market and democracy: fundamental tensions V. The democratization of the economy They talked about it Presentation of the book in the AGEFI, the daily newspaper of the Economic and Financial Agency in Geneva Book review on the website Alterinfos, América Latina
Political Science
Keywords: Bolivia; solidarity economy

From Economy to Society: Perspectives on Transnational Risk Regulation - Lange, Bettina; Thomas, Dania; Sarat, Austin (Emerald Group Publishing, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity? Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks. KM - Parts I and II theoretically equgage specifically with Polanyi, and apply and develop Polanyian ideas.
Law; Sociology
Keywords: administrative law & regulatory practice; commercial law; comparative law; embeddedness; emotions; international law; international trade law; risk; self-regulating market

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Political Science; Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Philosophy; Political Science
Keywords: critical theory; feminism; feminist theory; triple movement

Towards an Economic Sociology of Law - Ashiagbor, Diamond; Kotiswaran, Prabha; Perry-Kessaris, Amanda (Wiley-Blackwell, 2013)
Reflecting a developing trend towards interdisciplinary research in economics and law, this agenda–setting volume makes the case for economic sociology of law an emerging field that draws on empirical, analytical and normative insights from sociology to investigate relationships between legal and economic phenomena. It locates this novel subject in a wider socio–legal tradition and identifies common ground between Polanyian and Weberian approaches to the law, economy, and society, despite the two theorists divergent views on the functionality of the capitalist model. The volume provides a platform for researchers critical responses to the social embeddedness of market societies. Contributors demonstrate the value of applying a combination of methods in their work, from heterogeneous disciplines such as legal history and ethnography. They consider the position in the western and developed nations, as well as in post–colonial polities. The resulting publication is a well–crafted primer on a specialism that, by combining the insights of socio–economic analysis with the formative influences exerted by their specific legal contexts, informs a more nuanced assessment of law, economics and society.
Law; Sociology
Keywords: WEBER; Max; 1864-1920; economic sociology; economic sociology of law; law

Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Humanities
Keywords: archaeology; business & economics; economic history; history / ancient / general

Karl Polanyi - Vail, John (Routledge, 2013)
Economics; Sociology
Keywords: business & economics / economics / theory

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Sociology; Political Science
Keywords: Europe; business & economics; commodification; economic theory; social policy

Socioéconomie et démocratie, l'actualité de Karl Polanyi - Hillenkamp, Isabelle; Laville, Jean-Louis (Toulouse : Érès éd, 2013)
La crise actuelle révèle des tensions fondamentales entre capitalisme et démocratie. L'orthodoxie occidentale, centrée sur les programmes d'ajustement, s'avère incapable d'affronter ce défi à la frontière de l'économie, du social et du politique. Il est temps de se tourner vers d'autres approches. S'appuyant sur l'oeuvre singulière de Karl Polanyi (1886- 1964) qui a décelé la dérive totalitaire de la société de marché, cet ouvrage soumet de nouvelles clés pour penser certains des problèmes les plus ardus de notre temps. Les auteurs, internationalement reconnus, venant d'Amérique et d'Europe, du Sud et du Nord, sont publiés pour la première fois ensemble en langue française. Ils proposent une vision croisée des rapports entre démocratie et économie, à partir de différentes disciplines et de divers terrains d'étude. Cette réflexion collective débouche sur la construction d'un cadre théorique permettant de comprendre la teneur des mutations économiques et politiques contemporaines. Mais elle ne s'arrête pas aux constats critiques. Face à la menace d'une régression autoritaire, elle s'intéresse aux pratiques qui concrétisent des issues solidaires et démocratiques à la crise. ENG: The aim of this book is to mobilize the contribution of Polanyi to think the socio-economy in a perspective of deepening democracy. The book updates the critical analysis of the new globalized capitalism but also identifies socio-economic experiences that can contribute to building more democratic societies in the 21st century.
Political Science; Development Studies
Keywords: démocratie; développement économique - aspect social; economics - sociological aspects; triple movement; économie de marché; économie politique - aspect sociologique; économie sociale; économie sociale et solidaire

A Handbook of Economic Anthropology, Second Edition - Carrier, James G. (Edward Elgar Publishing, 2012)
Acclaim for the first edition: 'The volume is a remarkable contribution to economic anthropology and will no doubt be a fundamental tool for students, scholars, and experts in the sub-discipline.' _ Mao Mollona, Journal of the Royal Anthropologica
Anthropology
Keywords: business & economics; cultural anthropology; cultural policy; economic anthropology; macroeconomics; political science; popular culture; public policy; social science

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio – Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Economics
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Law; Political Science
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Sociology; Geography
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Anthropology
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general

Understanding India’s New Political Economy: A Great Transformation? - Ruparelia, Sanjay; Reddy, Sanjay; Harriss, John; Corbridge, Stuart (Taylor & Francis, 2011)
A number of large-scale transformations have shaped the economy, polity and society of India over the past quarter century. This book provides a detailed account of three that are of particular importance: the advent of liberal economic reform, the ascendance of Hindu cultural nationalism, and the empowerment of historically subordinate classes through popular democratic mobilizations. Filling a gap in existing literature, the book goes beyond looking at the transformations in isolation, managing to: • Explain the empirical linkages between these three phenomena • Provide an account that integrates the insights of separate disciplinary perspectives • Explain their distinct but possibly related causes and the likely consequences of these central transformations taken together By seeking to explain the causal relationships between these central transformations through a coordinated conversation across different disciplines, the dynamics of India’s new political economy are captured. Chapters focus on the political, economic and social aspects of India in their current and historical context. The contributors use new empirical research to discuss how India’s multidimensional story of economic growth, social welfare and democratic deepening is likely to develop. This is an essential text for students and researchers of India's political economy and the growth economies of Asia.
Economics
Keywords: India; business & economics; ethnic studies

Il sofisma economicista: intorno a Karl Polanyi - Caillé, Alain (sn, 2011)
KM translate: "The economic sophistry" and "The two meanings of" economic "", short writings by Karl Polanyi published here partially in a version taken from the French magazine MAUSS, represent a wonderful example of critical synthesis and set of depth of analysis, an analysis that comes to the conviction of the anthropological and social disaster caused not only by liberalism, but even more by the fallacy of an entire system of thought, economic science, which seeks to justify and support it. In support of the interesting pages of Polanyi, this book presents two contributions, respectively by Alain Caillé with Jean-Louis Laville and Jerome Maucourant, which, in addition to quickly presenting the intellectual biography of the Hungarian philosopher, clarify the extreme relevance of his critique of capitalism and the society of the markets. Polanyi emerges as an economist from the solid historical and anthropological foundations that, with his work, has been able to dismantle the apparently solid building of the classical economy to reveal its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century.
Sociology
Keywords: business & economics; economic theory

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Law; Political Science
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

The Globalization of Addiction: A Study in Poverty of the Spirit - Alexander, Bruce (Oxford University Press, 2010)
'The Globalization of Addiction' presents a radical rethink about the nature of addiction. Scientific medicine has failed when it comes to addiction. There are no reliable methods to cure it, prevent it, or take the pain out of it. There is no durable consensus on what addiction is, what causes it, or what should be done about it. Meanwhile, it continues to increase around the world. This book argues that the cause of this failure to control addiction is that the conventional wisdom of the 19th and 20th centuries focused too single-mindedly on the afflicted individual addict. Although addiction obviously manifests itself in individual cases, its prevalence differs dramatically between societies. For example, it can be quite rare in a society for centuries, and then become common when a tribal culture is destroyed or a highly developed civilization collapses. When addiction becomes commonplace in a society, people become addicted not only to alcohol and drugs, but to a thousand other destructive pursuits: money, power, dysfunctional relationships, or video games. A social perspective on addiction does not deny individual differences in vulnerability to addiction, but it removes them from the foreground of attention, because social determinants are more powerful. This book shows that the social circumstances that spread addiction in a conquered tribe or a falling civilisation are also built into today's globalizing free-market society. A free-market society is magnificently productive, but it subjects people to irresistible pressures towards individualism and competition, tearing rich and poor alike from the close social and spiritual ties that normally constitute human life. People adapt to their dislocation by finding the best substitutes for a sustaining social and spiritual life that they can, and addiction serves this function all too well. The book argues that the most effective response to a growing addiction problem is a social and political one, rather than an individual one. Such a solution would not put the doctors, psychologists, social workers, policemen, and priests out of work, but it would incorporate their practices in a larger social project. The project is to reshape society with enough force and imagination to enable people to find social integration and meaning in everyday life. Then great numbers of them would not need to fill their inner void with addictions.
Psychology
Keywords: clinical psychology; disease & health Issues; psychiatry; psychology; psychopharmacology; public health; social science

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Sociology; Political Science
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

Karl Polanyi: the limits of the market - Dale, Gareth (Polity Press, 2010)
Karl Polanyi: The Limits of the Market is the first comprehensive introduction to Polanyi's ideas and legacy. It assesses not only the texts for which he is famous – prepared during his spells in American academia – but also his journalistic articles written in his first exile in Vienna, and lectures and pamphlets from his second exile, in Britain. It provides a detailed critical analysis of The Great Transformation, but also surveys Polanyi’s seminal writings in economic anthropology, the economic history of ancientand archaic societies, and political and economic theory. Its primary source base includes interviews with Polanyi's daughter, Kari Polanyi-Levitt, as well as the entire compass of his own published and unpublished writings in English and German. This engaging and accessible introduction to Polanyi's thinkingwill appeal to students and scholars across the social sciences,providing a refreshing perspective on the roots of our currenteconomic crisis.
Political Science
Keywords: economics; philosophy

Transformation als historischer Prozess: Karl Polanyi - Rebmann, Mara; Marmuth, Juliane (GRIN Verlag, 2010)
KM translate: Polanyi starts from the thesis that only the emergence of a liberal market economy with its "free play of the forces" led to that characteristic "separation" and self-sufficiency of the economy against society, which historically represents a novelty and bourgeois society of all others Distinguishes social information. With this thesis, the complex transformation of societies through the interaction with the economic order on the basis of Polanyi's work The Great Transformation will be descriptively explained and discussed. Here are his theses taken up and explained from his point of view.
Political Science
Keywords: Great Transformation; The (Book)

Challenging Neoliberalism in Latin America - Silva, Eduardo (Cambridge University Press, 2009)
At the turn of the twentieth century, a concatenation of diverse social movements arose unexpectedly in Latin America, culminating in massive anti-free market demonstrations. These events ushered in governments in Argentina, Bolivia, Ecuador, and Venezuela that advocated socialization and planning, challenging the consensus over neoliberal hegemony and the weakness of movements to oppose it. Eduardo Silva offers the first comprehensive comparative account of these extraordinary events, arguing that the shift was influenced by favorable political associational space, a reformist orientation to demands, economic crisis, and mechanisms that facilitated horizontal linkages among a wide variety of social movement organizations. His analysis applies Karl Polanyi's theory of the double movement of market society to these events, predicting the dawning of an era more supportive of government intervention in the economy and society.
Political Science
Keywords: Latin America; double movement; market society; neoliberalism; political science / comparative politics; political science / world / general

The Extended Case Method: Four Countries, Four Decades, Four Great Transformations, and One Theoretical Tradition - Burawoy, Michael (University of California Press, 2009)
In this remarkable collection of essays, Michael Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the twentieth century—the rise and fall of the Soviet Union and its satellites, the reconstruction of U.S. capitalism, and the African transition to post-colonialism in Zambia. Burawoy's odyssey began in 1968 in the Zambian copper mines and proceeded to Chicago's South Side, where he worked as a machine operator and enjoyed a unique perspective on the stability of advanced capitalism. In the 1980s, this perspective was deepened by contrast with his work in diverse Hungarian factories. Surprised by the collapse of socialism in Hungary in 1989, he journeyed in 1991 to the Soviet Union, which by the end of the year had unexpectedly dissolved. He then spent the next decade studying how the working class survived the catastrophic collapse of the Soviet economy. These essays, presented with a perspective that has benefited from time and rich experience, offer ethnographers a theory and a method for developing novel understandings of epochal change.
Sociology
Keywords: social science; sociology

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Anthropology; History
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Karl Polanyi's Great Transformation and Development Politics - Deutschmann, Moritz (Grin Verlag, 2009)
English, abstract: Attempts to understand the transformation processes in the developing world have often led to a closer examination of Europe′s and America′s own history, as many theories of development suggest a specific interpretation of these histories: Modernization theorists, for example, see Europe′s and America′s history mainly as a straightforward progression towards welfare and democracy, eclipsing the aspects that do not fit into this picture, like the World Wars or the American Civil War. Therefore, although Karl Polanyi′s "The Great Transformation" treats mainly historical events in Europe, it can at the same time be an important contribution to our understanding of the economic and social transformations in the developing world. In this essay, I will first try to make clear, what assumptions underlie Polanyi′s argument and what he means by the notion of "market society." I will proceed in three steps: first, I will explore the different roles that the economy, according to Polanyi, plays in capitalist and pre-capitalist societies; I will look then at the historical processes that led to the rise of a "market society." Finally, I will discuss the political reactions to these processes which can be characterized, in Polanyi′s view, by a "double movement." As Polanyi is one of the most important critics of economic liberalism, it is helpful to compare his account of the "Great Transformation" to a second, even more influential anti-liberal perspective, Marxism. Apart from some similarities, the fundamental difference seems to be that Polanyi does not give a positive account of modernization. This leads to the question, how Polanyi′s theori
Political Science
Keywords: Great Transformation; The (Book); development; double movement; market society; modernization

Co-operatives in a Global Economy: The Challenges of Co-operation Across Borders - Reed, Darryl; McMurtry, J. J. (Cambridge Scholars Publishing, 2008)
In their efforts to internationalize in the emerging global economy, co-operatives not only face a variety of problems that are common to all firms, but encounter specific challenges due to their particular value commitments, forms of incorporation and organizational structures. These features of cooperatives are generally seen as a major source of competitive disadvantages and may cause significant trade-offs, forcing cooperatives to choose between living up to their principles of member ownership and control and remaining economically viable. Critics argue that such trade-offs signal the increasing irrelevance of cooperatives in a global economy. Advocates, however, counter that cooperatives may have unique competitive advantages which can be exploited in a global economy and that current trade-offs facing cooperatives can be overcome with the development of new international and transnational cooperative institutions and practices. Cooperatives, they claim, represent a much more sustainable and equitable form of production and may form the basis for viable, alternative approaches to development. This collection examines these debates about the roles of cooperatives in our increasingly global economy.
Economics
Keywords: business & economics; business & economics - international; co-operatives; globalization; social economy; social science - developing and emerging countries

The Institutions of the Market: Organizations, Social Systems, and Governance - Ebner, Alexander; Beck, Nikolaus (OUP Oxford, 2008)
This book approaches markets as a dynamic ensemble of institutions; and as a set of rules or norms, that contribute to the evolution of social systems of governance, and can be analysed as a structured social system. It tackles such questions as: * Where do markets come from and what drives their evolution? * How do organizations cope with the competitive dynamism of markets? * What is the role of governance mechanisms in the institutional coordination of markets? Using this 'new institutionalist' approach, an international group of leading scholars examine the institutional foundations of economic change. Drawn from an array of disciplines, including Business, Organization Studies, Economics, and Sociology, the contributors address the organizational capabilities of firms, the social structuration of competition, and the diversity of governance mechanisms in the market. Contributors include: Nikolaus Beck, Christophe Boone, Robert Boyer, Alexander Ebner, Neil Fligstein, Henrich R. Greve, John Harriss, Bob Hinings, Geoffrey M. Hodgson, Bob Jessop, Alfred Kieser, Namrata Malhotra, Renate E. Meyer, Richard R. Nelson, Rudolf Richter, Peter Walgenbach, Filippo Carlo Wezel, Sidney G. Winter, and Arjen Van Witteloostuijn.
Economics
Keywords: business & economics; competitive dynamism; economics; evolution of markets; governance mechanisms; institutional coordination; management; markets; new institutionalist approach; organizational capabilities; social structuration

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Sociology; Political Science
Keywords: ARENDT; Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).
History

America transformed: globalization, inequality, and power - Hytrek, Gary J.; Zentgraf, Kristine M. (Oxford University Press, Incorporated, 2008)
Globalization–the interconnection of the world culturally, socially, politically, and economically–has generated intense theoretical and practical concerns. Is globalization inevitable? What are the effects of globalization on social structures and individual perceptions? What is the effect of globalization on societal level inequality? America Transformed: Globalization, Inequality, and Power examines these questions by analyzing the links among global processes and shifting patterns of stratification, inequality, and social mobility in the United States. While many texts separate discussions of macro- and micro-level processes when examining globalization, this book skillfully integrates general macro-level processes with specific reference to the micro-level effects of globalization in the U.S. Exploring the critical dimensions of inequality–class, gender, and immigration–America Transformed situates the U.S. experience within the broader global context, and fleshes out the mechanism through which global processes affect social stratification. By examining the social construction of globalization, the authors identify the key policy challenges of globalization, and some of the innovative community-based responses to social inequality.America Transformed provides powerful insights into the contested dialectical relationship between global and local forces: how globalization shapes stratification and inequality in the U.S., and how local communities attempt to mediate those changes.
Political Science
Keywords: globalization; social classes; social science / sociology / general

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Political Science; Sociology
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

Against the Law: Labor Protests in China’s Rustbelt and Sunbelt - Lee, Ching Kwan (University of California Press, 2007)
This study opens a critical perspective on the slow death of socialism and the rebirth of capitalism in the world's most dynamic and populous country. Based on remarkable fieldwork and extensive interviews in Chinese textile, apparel, machinery, and household appliance factories, Against the Law finds a rising tide of labor unrest mostly hidden from the world's attention. Providing a broad political and economic analysis of this labor struggle together with fine-grained ethnographic detail, the book portrays the Chinese working class as workers' stories unfold in bankrupt state factories and global sweatshops, in crowded dormitories and remote villages, at street protests as well as in quiet disenchantment with the corrupt officialdom and the fledgling legal system.
Anthropology
Keywords: China; cultural anthropology; double movement; fictitious commodities; labour; social anthropology

The Transnational Politics of Corporate Governance Regulation - Overbeek, Henk; Apeldoorn, Bastiaan van; Nölke, Andreas (Routledge, 2007)
This ambitious volume explores the politics of recent changes in corporate governance regulation and the transnational forces driving the process. Corporate governance has in the 1990s become a catchphrase of the global business community. The Enron collapse and other recent corporate scandals, as well as growing worries in Europe about the rise of Anglo-Saxon finance, have made issues of corporate governance the subject of political controversies and of public debate. The contributors argue that the regulation of corporate governance is an inherently political affair. Given the context of the deepening globalization of the corporate world, it is also increasingly a transnational phenomenon. In terms of the content of regulation the book shows an increasing reliance on the application of market mechanisms and a tendency for corporations themselves to become commodities. The emerging new mode of regulation is characterized by increasing informalization and by forms of private regulation. These changes in content and mode are driven by transnational actors, first of all the owners of internationally mobile financial capital and their functionaries such as coordination service firms, as well as by key public international agencies such as the European Commission. The Transnational Politics of Corporate Governance Regulation will be of interest to students and researchers of international political economy, politics, economics and corporate governance.
Political Science
Keywords: NGOs; NGOs (non-governmental organizations); business & economics; economic policy; international political economy; political science; public policy

Reading Karl Polanyi for the Twenty-First Century - Bugra, A. (Palgrave Macmillan, 2007)
Using Karl Polanyi's analysis of the separation of politics and the economy, the book argues that the market economy is not a spontaneous process, but a...
Economics; Sociology
Keywords: commodification; financial economics; macroeconomics; market economy; monetary economics

Third Ways: How Bulgarian Greens, Swedish Housewives, and Beer-swilling Englishmen Created Family-centered Economies– and why They Disappeared - Carlson, Allan C. (ISI Books, 2007)
Freewheeling capitalism or collectivist communism: when it came to political-economic systems, did the twentieth century present any other choice? Does our century? In Third Ways, social historian Allan Carlson tells the story of how different thinkers from Bulgaria to Great Britain created economic systems during the twentieth century that were by intent neither capitalist nor communist. Unlike fascists, these seekers were committed to democracy and pluralism. Unlike liberal capitalists, they refused to treat human labor and relationships as commodities like any other. And unlike communists, they strongly defended private property and the dignity of persons and families. Instead, the builders of these alternative economic systems wanted to protect and renew the “natural” communities of family, village, neighborhood, and parish. They treasured rural culture and family farming and defended traditional sex roles and vital home economies. Carlson's book takes a fresh look at distributism, the controversial economic project of Hilaire Belloc and G. K. Chesterton which focused on broad property ownership and small-scale production; recovers the forgotten thought of Alexander Chayanov, a Russian economist who put forth a theory of “the natural family economy”; discusses the remarkable “third way” policies of peasant-led governments in post–World War I Bulgaria, Poland, and Romania; recounts the dramatic and largely unknown effort by Swedish housewives to defend their homes against radical feminism; relates the iconoclastic ideas of economic historian Karl Polanyi, including his concepts of “the economy without markets” and “the great transformation”; and praises the efforts by European Christian Democrats to build a moral economy on the concept of homo religious—“religious man.” Finally, Carlson's work explains why these efforts—at times rich in hope and prospects—ultimately failed, often with tragic results. The tale inspires wistful regret over lost opportunities that, if seized, might have spared tens of millions of lives and forestalled or avoided the blights of fascism, Stalinism, socialism, and the advent of the servile state. And yet the book closes with hope, enunciating a set of principles that could be used today for invigorating a “family way” economy compatible with an authentic, healthy, and humane culture of enterprise.
History; Economics
Keywords: business & economics; economic history; economic theory; economics / comparative; history - modern; history / 20th Century

Beyond the boycott: labor rights, human rights, and transnational activism - Seidman, G. (Russell Sage Foundation, 2007)
Sociology
Keywords: business & economics - international; business & economics / business ethics; law / labor & employment; political science / human rights; political science / labor & industrial relations; political science / labour & industrial relations; social science - developing and emerging countries; social science / sociology / general

Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Political Science; History
Keywords: countermovement; globalization; political economy; political science

Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Political Science
Keywords: international political economy; international relations

Vulnerability and violence: the impact of globalisation - Kirby, Peadar (Pluto, 2006)
'Vulnerability' is now a key term in globalisation studies. It is used to describe how globalisation impacts on individual security, local communities and even global flows of trade, finance and investment. Yet there has been little attempt to interrogate the term and what it is trying to express about globalisation.Peadar Kirby examines what is really meant by 'vulnerability' and links it to new forms of violence that have resulted from decreased security and social cohesion. He argues that vulnerability and violence are characteristic features of a new world order dominated by neoliberal globalisation. Illustrating his argument with a wealth of examples taken from all over the world – from the sudden collapse of the middle class in Argentina to increased levels of poverty internationally – he offers a robust theoretical grounding that will be of use to anyone studying vulnerability and violence and their relation to contemporary globalisation.
Political Science
Keywords: globalization; globalization - economic aspects; globalization - social aspects; international security; national security; political freedom & security; violence; violence in society

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
History; Political Science
Keywords: autobiography; biography; business & economics

Lavoro e società industriale. Da Adam Smith a Karl Polanyi - Rosa, Michele La; Rizza, Roberto; Zurla, Paolo (FrancoAngeli, 2006)
KM translate: The volume aims to provide a contribution to the knowledge of the ways of birth and consolidation of the sociological discourse on the economy, at work and their transformations connected to the process of industrialization. The goal, mainly educational, is pursued through the analysis of the contributions that Karl Marx, Emile Durkheim, Max Weber, Joseph Schumpeter, Karl Polanyi, Frederick Taylor and Elton Mayo have offered in this regard. The treatment of these authors, whose total or partial belonging to the sociological context is out of the question, was preceded by a brief analysis of others such as Adam Smith, Charles Babbage and Andrew Ure who, although not strictly belonging to this disciplinary area,
Economics; Sociology
Keywords: DURKHEIM; Emile; MARX; Karl; 1818-1883; SMITH; Adam; 1723-1790; business & economics - labor; economic sociology; industrial revolution; industrialization; sociology of work

Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o 1
History
Keywords: CHAPMAN; Anne; POLANYI LEVITT; Kari; ZEMON DAVIS; Nathalie

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Geography; Political Science
Keywords: GILL; Stephen; political science / globalization; political science / reference

Citizenship unbound: The global politics of neo-liberalism and labor migration - Barker, Isabelle Virginie; Cornell, Drucilla (2005)
This dissertation considers the status of citizenship in an era of neo-liberal globalization. Citing increased labor migration and the retreat of domestic social policies throughout the world as intersecting processes, I argue that narratives of national citizenship lie at the heart of this intersection, transformed by rapidly changing geopolitical conditions. Despite challenges, national citizenship remains a relevant political category, though reformulated along the lines of neo-liberal principles of privatization, market rationality, and individual responsibility. the politics and rhetoric surrounding the 1996 federal reforms of immigration and social policy in the United States serve as one example of this process. I further support my claim with an extensive illustration of the linkages between the restructuring of U.S. health care policy for senior citizens with the increased migration of women from the global South to provide low-wage direct care services for the aging population in the United States. I then evaluate the work of Martha Nussbaum, Amartya Sen and Thomas Pogge, arguing that their respective efforts fail to offer effective interventions into the fate of democratic citizenship in an era defined by expanding inequalities and shrinking public spaces. I conclude by bringing together the works of Karl Polanyi, David Held, and Hannah Arendt with feminist scholarship to develop a feminist theory of democracy and political membership for the twenty-first century. (Copyright applies to all Abstracts.)
Political Science
Keywords: ARENDT; Hannah; HELD; David; NUSSBAUM; Martha; POGGE; Thomas; SEN; Amartya; citizenship; feminist theory; globalization; labour migration; political science; women's studies

The Economy as a Polity: The Political Constitution of Contemporary Capitalism - Joerges, Christian; Stråth, Bo; Wagner, Peter (Psychology Press, 2005)
The debate about so-called economic globalization has reached a new phase. The hegemony of neo-liberal thinking has ended, in the face of both the increased and increasingly effective resistance to the social consequences of neo-liberal market-making - rising inequality and insecurity throughout the world - and the visibly dysfunctional effects of lack of regulation - currency and stock market crashes, among others. Thus, the story about 'the rise and fall of market society', which was first told in these terms by Karl Polanyi sixty years ago, is about to receive a new chapter. In this light, this volume offers a novel perspective on the interaction between states and markets. In contrast to much of current theoretical wisdom, we hold, with Polanyi, that markets cannot even be consistently thought of as self-regulating. Markets are always constituted by framework conditions that cannot be set by the markets themselves. The range and scope of market rules requires some agreement, or at least acceptance, for economic exchange to be working at all; in democratic societies, these rules are at least theoretically always subject to political debate and decision. To put the issue in theoretical terms: even the most pure version of economic liberalism always entails at the same time a political philosophy. This volume, thus, proposes to understand contemporary capitalism by regarding the economy as a polity, as an arrangement that is always constituted by some collective agreements about its mode of operation. Such theoretical position on its own, though, is insufficient to explain the workings of capitalism once and for all. Historical experiences with capitalism have led to transformations that require new angles of analysis. It is in the nature of the struggles over the embedding of markets that their outcomes are subject to historical contingency and cannot be completely known beforehand. Beyond a review of the theoretical tools at hand, therefore, the analysis of the contemporary constellation of capitalism, also requires an understanding of its recent transformations. This is the second task to which this volume is devoted - through analyses of the current state of regulation of labour and money and through investigations of the historical development and novel forms of the mode of embedding markets. While focusing on the renewal of the analysis of contemporary capitalism, the volume also points to fruitful directions of institutional or policy change and provides perspectives for a much-needed political renewal, with a particular focus on the European Union as a novel polity embedding the European economy.
Political Science; Economics
Keywords: business & economics; economic policy; free enterprise; public policy

Ancient Athens & modern ideology: value, theory & evidence in historical sciences : Max Weber, Karl Polanyi & Moses Finley - Nafissi, Mohammad (Institute of Classical Studies, School of Advanced Study, University of London, 2005)
History; Classical Studies
Keywords: Athens (Greece); WEBER; Max; 1864-1920; civilization; classical civilization; classical philology; economic theory; economics; history / ancient / Greece; social science / sociology / general

Surviving Capitalism: How We Learned to Live with the Market and Remained Almost Human - Ringmar, Erik (Anthem Press, 2005)
Human life cannot be reduced to market transactions and human beings cannot only be treated as economic actors. When the power of the market increases, human beings will always try to protect themselves. Given the differences that exist in social and cultural traditions, these protective responses are likely to differ from one society to the other. This is why, even in a global market, diversity is always likely to persist. This book investigates the question of economic globalization - whether it is likely to lead to full convergence between political models and ways of life, or whether, even in a completely globalized world economy, there is likely to be scope for alternative solutions. But in a fully globalized world, how will we survive capitalism?
Political Science
Keywords: economic globalization; globalization

International Relations and the Problem of Difference - Inayatullah, Naeem; Blaney, David L. (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other. KM: Chapter 5 "Toward an Ethnological IPE" deals extensively with Polanyi's ideas
Political Science
Keywords: economic anthropology; ethnological IPE; international political economy; international relations; political economy

Environmental Values in a Globalizing World: Nature, Justice and Governance - Lowe, Ian; Paavola, Jouni (Routledge, 2004)
This multidisciplinary volume presents a refreshing new approach to environmental values in the global age. it investigates the challenges that globalization poses to traditional environmental values in general as well as in politics and international governance.Divided into five parts, the book investigates how environmental values could be reconceived in a globalizing world.Part I explores contemporary environmental values and their implications for a globalizing world.Part II examines the development of Western and Eastern environmental valuesPart III discusses contemporary environmental politicsPart IV examines how values inform environmental governance and how governance solutions influence which values are realisedPart V concludes the volume with two different views of the prospects of environmental values in a globalising world. This study will be of great interest to students and researchers studying the environment in philosophy, political science, international relations, international environment law, environmental studies and development studies. KM - Contains chapter: "Global Liberalism, Environmentalism, and the Changing Boundaries of the Political : Karl Polanyi's Insights" by John M. Meyer
Political Science
Keywords: MEYER; John M.; environmental policy; globalization; public policy

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (Cambridge University Press, 2004)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Political Science
Keywords: Europe; history; international relations; political science - history and theory

The Meaning of Freedom in a Complex Society: The Development of Karl Polanyi's Thought on Economics, Modernity, and Human Liberty - Katsh, Gabriel (Harvard University, 2004)
Political Science
Keywords: freedom in a complex society

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Sociology; Political Science
Keywords: ARENDT; Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Changing employment protection systems : Karl Polanyi's "Double Movement" and the evolution of federal labour standards in Australia 1979 to 2000 - Michelotti, Marco (Association of Industrial Relations Academics of Australia and New Zealand, 2004)
Yes
Management Studies; Business Studies
Keywords: Australia; double movement; industrial relations; labour standards

Globalization: People, Perspectives, and Progress - Mott, William H. (Greenwood Publishing Group, 2004)
This study expands the narrow economic-commercial focus of the topical media and places globalization in a multidisciplinary context as a continuing process and a permanent condition that transforms human living and society. Early chapters review the development of globalization as creating and diffusing knowledge, expanding people's perspectives on living, and continuing progress. These chapters introduce globalization as an iterative, human, and deliberate process of creating new knowledge and using it to reinterpret the world, time, and man's place in both. The later chapters present the major analytical perspectives of globalization–political, cultural, and economic–and a comparison of the primary carriers of globalism and barriers to globalization.Drawing on classical and modern analysis, as well as narrow, topical journalism, the work focuses each perspective on people through the human processes of creating knowledge and living together. The work expands the economic perspective beyond the fashionable focus on trade and investment into the triggering and shadowing relationships between economic growth, political conflict, and social stress. The political perspective expands international politics and law to global governance, triadic dispute resolution, and global civil society. The cultural and antiglobal perspectives reflect the success of economic globalization in bringing people directly into the narrowly rational processes of international politics and economics. The final analytical chapter collects and compares observations and develops conclusions about globalization across the several perspectives. Speculation about alterative futures for globalizing humanity can constitute a coherent standard, ideal, or direction for policymaking, or an agenda for continuing research and debate.
Political Science
Keywords: comparative politics; political science; social science

Democracy and the Global System: A Contribution to the Critique of Liberal Internationalism - Biancardi, F. (Palgrave Macmillan UK, 2003)
Jacket abstract: "Democracy and the Global System analyses the relationship between liberal democracy and the global system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts, including Barrington Moore Jr., Karl Polanyi, Joseph Schumpeter, Samuel Huntington and David Held. While sympathetic to the aim of spreading liberal democracy globally, he demonstrates the many tensions and contradictions involved in achieving this outcome." Google books: What are the prospects of the liberal democratic form of state spreading throughout the world? Democracy and the Global System analyses the relationship between liberal democracy and the international system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts. While sympathetic to the aim of spreading liberal democracy, he demonstrates the many tensions and contradictions involved in achieving this outcome.
Political Science
Keywords: democracy; international relations; political ideologies; political science

Great Transformations: Economic Ideas and Institutional Change in the Twentieth Century - Blyth, Mark (Cambridge University Press, 2002)
Mark Blyth argues that economic ideas are powerful political tools as used by domestic groups in order to effect change since whoever defines what the economy is, what is wrong with it, and what would improve it, has a profound political resource in their possession. Blyth analyzes the 1930s and 1970s, two periods of deep-seated institutional change that characterized the twentieth century. Viewing both periods of change as part of the same dynamic, Blyth argues that the 1930s labor reacted against the exigencies of the market and demanded state action to mitigate the market's effects by "embedding liberalism" and the 1970s, those who benefited least from such "embedding" institutions, namely business, reacted against these constraints and sought to overturn that institutional order. In Great Transformations, Blyth demonstrates the critical role economic ideas played in making institutional change possible and he rethinks the relationship between uncertainty, ideas, and interests on how, and under what conditions, institutional change takes place. Mark Blyth is an assistant professor of political science at the Johns Hopkins University specializing in comparative political economy. He has taught at Columbia University, and at the University of Birmingham, UK. Blyth is a member of the editorial board of the Review of International Political Economy.
Political Science
Keywords: economic policy; political economy; political science; public policy

Chronik der grossen Transformation. Artikel und Aufsätze (1920-1945) / Wirtschaftliche Transformation, Gegenbewegung und der Kampf um die Demokratie - Cangiani, Michele; Thomasberger, Claus; Polanyi, Karl (Metropolis, 2002)
ENGLISH: In the last few years the interest in Karl Polanyi's work has been growing between 1920 and 1945, and with only a few exceptions they are difficult or impossible to access. The articles, essays, and manuscripts written in Vienna and England are not only the result of intensive studies during the central years of the author's life, but they are also the main part of his work. In this work, Polanyi analyzes a period decisive for the development of the twentieth century. The writings deal not only with the central problems and questions, the results of which are incorporated in his main work, The Great Transformation, published in 1944, without giving any further explicit insight, and thus provide an insight into the ideas, ideas, and reflections from which they emerged are. They are also (and above all) important time documents, significant as direct and immediate reflections on the political and economic events of the inter-war period. Polanyi analyzes with great care both the economic and political events, the global economic crisis as well as the international political situation, the attempts to create the conditions for peace and recovery, as well as the conflicts that point towards a new world war. The main topics for the Austrian economist include industrial restructuring, corporate tendencies, the rise of fascism and the transformation of the economic and political institutions in Great Britain and the USA during the New Deal period. These are supplemented by works on fundamental topics such as pricing, economic theory, sociology and the theory of socialism. All investigations are subject to a uniform, theoretically and politically fundamental question: How can - after the collapse of the liberal system of the 19th century such as the socialist hopes of the twenties - defend and expand democracy and freedom? The most important articles, essays and manuscripts, which were written in the period between 1920 and 1945, are grouped into three volumes according to their content. Volume I, entitled Economic Transformation, Counter-Movements and the Fight for Democracy, contains the analyzes on the areas of economy, global economic crisis and economic policy. The subject of Volume II is The international policy between the two world wars. Volume III, in which we have summarized the theoretical work on pricing, socialist economic analysis, Marxism, sociological theory, socialism, and democracy, is under the heading of freedom, democracy, and socialism. DEUTSCH: In den letzten Jahren wächst das Interesse an den Arbeiten, die Karl Polanyi zwischen 1920 und 1945 verfasste und die - mit wenigen Ausnahmen - bisher nur schwer oder gar nicht zugänglich sind. Die in Wien und in England geschriebenen Artikel, Aufsätze und Manuskripte sind nicht nur das Ergebnis intensiver Studien während der zentralen Jahre des Lebens des Autors, sie machen auch den Hauptteil seines Werkes aus. Polanyi analysiert in diesen Arbeiten eine für die Entwicklung des zwanzigsten Jahrhunderts entscheidende Periode. Die Schriften behandeln nicht nur die zentralen Problem- und Fragestellungen, deren Resultate, ohne erneut explizit aufgegriffen zu werden, in seinem 1944 publizierten Hauptwerk, The Great Transformation, einfließen, und geben damit Einblick in die Gedankengänge, Ideen und Überlegungen, aus denen jene hervorgegangen sind. Sie sind auch (und vor allen Dingen) wichtige Zeitdokumente, bedeutsam als direkte und unmittelbare Reflexionen über die politischen und wirtschaftlichen Ereignisse der Zwischenkriegsphase. Polanyi analysiert mit großer Sorgfalt sowohl die wirtschaftlichen wie auch die politischen Ereignisse, die Weltwirtschaftskrise wie die internationale politische Lage, die Versuche, die Bedingungen für Frieden und Aufschwung herzustellen, wie die Konflikte, die in Richtung eines neuen Weltkriegs weisen. Zu den Themen der hauptsächlich für den Österreichischen Volkswirt verfassten Artikel gehören die industrielle Restrukturierung, die korporativen Tendenzen, der Aufstieg des Faschismus sowie die Transformation der ökonomischen und politischen Institutionen in Großbritannien und in den USA während der Periode des New Deal. Diese werden ergänzt durch Arbeiten über grundsätzliche Themen wie Preisbildung, ökonomische Theorie, Soziologie und Theorie des Sozialismus. Allen Untersuchungen unterliegt eine einheitliche, theoretisch und politisch grundlegende Fragestellung: Wie können - nach dem Zusammenbruch des liberalen Systems des 19. Jahrhunderts wie der sozialistischen Hoffnungen der zwanziger Jahre - Demokratie und Freiheit verteidigt und ausgebaut werden?Die wichtigsten Artikel, Aufsätze und Manuskripte, die in der Periode zwischen 1920 und 1945 entstanden sind, werden nach inhaltlichen Schwerpunkten in drei Bände gruppiert. Band I, der die Überschrift Wirtschaftliche Transformation, Gegenbewegungen und der Kampf um die Demokratie trägt, enthält die Analysen zu den Themenbereichen Wirtschaft, Weltwirtschaftskrise und Wirtschaftspolitik. Gegenstand von Band II ist Die internationale Politik zwischen den beiden Weltkriegen. Band III, in dem wir die theoretischen Arbeiten zur den Fragen Preisbildung, sozialistische Wirtschaftsrechnung, Marxismus, soziologische Theorie, Sozialismus und Demokratie u.a. zusammengefasst haben, steht unter der Überschrift Freiheit, Demokratie und Sozialismus. InhaltMichele Cangiani und Claus ThomasbergerVorbemerkung9Marktgesellschaft und Demokratie: die Perspektive der menschlichen Freiheit. Karl Polanyis Arbeiten von 1920 bis 1945 11I.Politische Kämpfe in den zwanziger Jahren1.England und die Wahlen 462.Zur Krise der englischen Arbeiterbewegung513.Die neue Internationale564.Das Bergbauproblem in England635.Der englische Generalstreik726.Probleme des englischen Generalstreiks80II. Liberale Reformprojekte7.Liberale Wirtschaftsreformen in England908.Liberale Sozialreformer in England959.Schmalenbach und Liberalismus104III.Die Weltwirtschaftskrise10.Zur wirtschaftlichen Neuordnung Europas11011.Demokratie und Währung in England12012.MacDonald und die Wirtschaftspolitik12913.England auf der Waage13414.Kritik an Lausanne14215.Wirtschaft und Demokratie 14916.Weltinflationismus15517.Von Lausanne bis Washington16318.Brain-Trust siegt17019.Roosevelt zerschlägt die Konferenz178IV.Der Zusammenbruch der Demokratie in Deutschland und in Europa20.Gegenrevolution18621.Staatsgründung19322.Hitler und die Wirtschaft19923.Korporatives Österreich - eine funktionale Gesellschaft ?204V.Restrukturierung und Demokratie in England24.Wirtschaftsprogramm der Samuel-Liberalen21425.Ende der Slums21626.Englisches Stahlstatut21827.Technologische Arbeitslosigkeit22028.Elliot oder Empire ?22329.Probleme der Demokratie in England22630.Lohntarif-Bill in Lancashire22831.Lancashire im Fegefeuer23032.Lancashire als Menschheitsfrage23633.England überlegt24934.Labour und die Eisenindustrie25135.Gewerkschaftstagung in Weymouth25336.Labour in Southport25637.Tory-Planwirtschafter25938.Die Liberalen für Empirehandel261VI.New Deal39.Roosevelt im Verfassungskampf26440.Amerika im Schmelztiegel27141.Roosevelt im Kampf27942.T.V.A. - Ein amerikanisches Wirtschaftsexperiment28143.Arbeitsrecht in U.S.A.29044.Amerikanisches Gewerkschaftsgesetz verfassungsmäßig29145.Roosevelts strategischer Rückzug29346.Gewerkschaften in den U.S.A.295VII.Die Entwicklung in der Sowjetunion47.Zweiter Fünfjahresplan abgebremst29848.Wo hält Sowjetrußland?30849.Russischer Verfassungswandel316
History
Keywords: Polanyi essays

All you can eat: greed, lust, and the new capitalism - McQuaig, Linda (Penguin, 2001)
Explains the mired history of social and economic thinking that has culminated in the new capitalism. McQuaig argues that instead of shaping our society to fit the economy, we must shape the economy to fit the society we want. 2001.
Economics
Keywords: business & economics; capitalism; capitalism - history; economic history; free enterprise; political science

Constructing a European Market: Standards, Regulation, and Governance - Egan, Michelle P. (Oxford University Press, 2001)
'An excellent contribution to our understanding of the political construction of markets... This is a well-written book, enjoyable to read as well as being very informative. I view this volume as a 'must read' for all scholars and graduate students in the areas of government and business, the politics of market economies and comparative politics in general. Michelle Egan's description and explanation of market construction and its impact on business standards, regulation and governance will be valuable to all of us for many, many years to come.' -Henry Jacek, McMaster University; Polibus: Newsletter of the IPSA Research CommitteeThis book provides a detailed analysis of the policies and institutions used by the EU to create a single market. Through a historical overview, sectoral case studies, and an assessment of recent policy initiatives, the author provides a comprehensive account of the evolution of European economic integration.
Political Science; Economics
Keywords: European Court of Justice; European Union; United States; business & economics; economic policy; harmonization; market integration; mutual recognition; public policy; regulation; single market; standards; trade barriers

Naukratis: Trade in Archaic Greece - Möller, Astrid (Oxford University Press, 2000)
Archaic Naukratis was a busy trading place in the Western Delta of the Nile, renowned for its sanctuaries and courtesans, granting the Greeks access to Egyptian grain and luxury items. Now, more than one hundred years after the discovery and excavation of Naukratis, the author offers the first full-length analysis of the archaeology and archaic history of this important site. Although Naukratis always features in modern accounts of ancient Greek colonization, it was not a place where the Greeks could freely establish their own political and social organization–it was under the strict control of the Egyptian pharaoh and his officials. To understand the special status of Naukratis, the author takes the port of trade model, surveying the political, social, and economic background of both Late Period Egypt and archaic Greece. A major section of the book comprises an archaeological re-evaluation of the topography of archaic Naukratis and its material finds. The sanctuaries, archaic pottery styles, terracottas, faiences, statuettes, and other small finds are examined in the light of recent scholarship, and an in-depth study of the literary evidence is brought to bear on the archaeological material. This book comprises a significant contribution to our understanding of Graeco-Egyptian relations during the seventh and sixth centuries BC and also demonstrates that Polanyian economic theory can play an invaluable rï¿½le in the ongoing debate about the concepts best employed to analyse the ancient Greek economy.
History; Archaeology
Keywords: Ancient Egypt; business & economics; economic history; history

The Rise of the Capital-State and Neo-Nationalism: A New Polanyian Moment - Svitych, Oleksandr (Brill, 2022)
Political Science
Keywords: critical social sciences; global studies; neo-nationalism; populism; social sciences; sociology & anthropology

Karl Polanyi and the Paradoxes of the Double Movement - Vail, John (Routledge, 2022)
This book offers a critical reconstruction of the double movement, the central thesis of Karl Polanyi’s The Great Transformation, one of the most influential books of the 20th century. The double movement is the establishment of a free market economy and the subsequent effort by society to ameliorate the destructive effects of the market. In Polanyi’s bold vision, the double movement constituted the hidden gear of social change and historical transformation within capitalism. The book is a forensic examination and critique of Polanyi’s argument. It develops an interpretive framework of the double movement as four interrelated social processes: the establishment of the self-regulating market, the rise of a market society that deepens and extends market imperatives, a social protection phase that constrains the market and safeguards society, and the contradictions and crises that result from this clash of social principles. The book will be an indispensable guide for students and scholars across the social sciences which illuminates the relevance of Polanyi’s insights to a critical understanding of the contemporary era –the scourge of insecurity and inequality, the multiple crises of neoliberalism, the rise of right wing populism- as well as those interested in egalitarian and emancipatory alternatives to capitalism.
Keywords: double movement; market society

Institutional Economics: Perspectives and Methods in Pursuit of a Better World - Whalen, Charles J. (Routledge, 2021)
Institutional economics is a sociocultural discipline and policy science which draws on the idea that economies are best understood through an appreciation of history, real-world institutions, and socioeconomic interrelations. This book brings together leading institutionalists to examine the tradition’s most essential perspectives and methods. The contributors to the book draw on a broad range of institutional thought from the classic work of Thorstein Veblen, John R. Commons, and Karl Polanyi, to the newer viewpoints of post-Keynesian institutionalism, feminist institutionalism, and environmental institutionalism. Methods range from frameworks used to analyze public policy and institutional change, to modes of analysis including myth busting, historically grounded narratives, and computer-based simulations. Each chapter surveys the origins, development, key features, applications, and frontiers of a particular viewpoint, framework, or mode of analysis. Due consideration is given to both strengths and weaknesses; and woven into the chapters is attention to core institutionalist concepts, including technology, institutions, culture, and complexity. The book provides economists with promising starting points for new research, students with contributions refreshingly in touch with the real world, and policymakers and social scientists with compelling reasons for engaging further with the institutionalist tradition.
Economics
Keywords: economic history; economic theory; institutional economics

Constituting the Political Economy of the Kurds: Social Embeddedness, Hegemony, and Identity - Tekdemir, Omer (Routledge, 2021)
This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late-Ottoman Empire, the initial Republican Turkey era, and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism.
Political Science
Keywords: Kurdistan; Political Science / World / Middle Eastern; embeddedness; ethnic studies; middle eastern studies; regional studies

Karl Polanyi and the Contemporary Political Crisis: Transforming Market Society in the Era of Climate Change - Kirby, Peadar (Bloomsbury Publishing, 2020)
Has politics reached breaking point? Rather than defending liberalism or abandoning it, how can a socially just and ecological alternative be built? Peadar Kirby investigates the causes of our current multifaceted global crisis by drawing on the work of Karl Polanyi. This book explores Polanyi's theory that social disruptions result from the attempt to run society according to the rules of the market. Drawing on these ideas, it outlines pathways towards an alternative future that overcome weaknesses in Marxism. Linking the ecological, political and socio-economic crises, Kirby identifies that an alternative socio-ecological model is emerging, consistent with the insights of Polanyi. Karl Polanyi and the Contemporary Political Crisis is an urgent intervention into key debates on the future of politics, on the low-carbon transition, on automation and on the emerging world order.
Keywords: climate change; ecological crisis

Karl Polanyi and Twenty-first-century Capitalism - Desai, Radhika; Levitt, Kari Polanyi (Manchester University Press, 2020)
As far right movements, social disintegration and international conflict emerge from the decay of the neoliberal order, Karl Polanyi's warnings against the unbridled domination of markets, is ever more relevant. The essays in Karl Polanyi for the 21st Century extend the boundaries of our understanding of Polanyi's life and work. They will interest Polanyi scholars and all interested in socialism and our future after neoliberalism. One asks whether, following Keynes and Hayek, Polanyi's ideas will shape the twenty-first century. Some clarify, for the meaning of money as a fictitious commodity. Others resolve difficulties in understanding the building blocks of Polanyi's thought: fictitious commodities, the double movement, the United States' exceptional development, the reality of society, and socialism as freedom in a complex society. And yes others explore how Polanyi sheds light on income inequality, world systems theory, comparative political economy.
Keywords: capitalism; double movement; neoliberalism; reality of society; socialism

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Sociology
Keywords: Great Transformation; The (Book); fictitious commodities

Economics as Social Science: Economics imperialism and the challenge of interdisciplinarity - Marchionatti, Roberto; Cedrini, Mario (Taylor & Francis, 2016)
There is a growing consensus in social sciences that there is a need for interdisciplinary research on the complexity of human behavior. At an age of crisis for both the economy and economic theory, economics is called upon to fruitfully cooperate with contiguous social disciplines. The term ‘economics imperialism’ refers to the expansion of economics to territories that lie outside the traditional domain of the discipline. Its critics argue that in starting with the assumption of maximizing behaviour, economics excludes the nuances of rival disciplines and has problems in interpreting real-world phenomena. This book focuses on a territory that persists to be largely intractable using the postulates of economics: that of primitive societies. In retracing the origins of economics imperialism back to the birth of the discipline, this volume argues that it offers a reductionist interpretation that is poor in interpretative power. By engaging with the neglected traditions of sociological and anthropological studies, the analysis offers suggestions for a more democratic cooperation between the social sciences. Economics as Social Science is of great interest to those who study history of economic thought, political economy and the history of economic anthropology, as well as history of social sciences and economic methodology.
Keywords: economic theory; economics imperialism